2006
DOI: 10.1021/jp056321k
|View full text |Cite
|
Sign up to set email alerts
|

Bundling and Diameter Selectivity in HiPco SWNTs Poly(p-phenylene vinylene-co-2,5-dioctyloxy-m-phenylene vinylene) Composites

Abstract: Temperature-dependent (TD) Raman measurements at laser excitation 514.5 nm were performed at different concentrations. The spectral profile of the radial breathing modes were investigated up to a polymer concentration of 1 g/L and were found to be dominated by approximately 1.2-1.4 nm diameter tubes at room temperature. Upon heating above the glass transition of the polymer (60 degrees C) the smaller tubes around approximately 0.9 nm increased significantly in relative intensity. This suggests that below the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…If the agent can recognize the electrical property and/or structural character of SWNTs, separation of SWNTs can be realized through the extraction [123]. The solubilizing agents reported so far include simple molecule such as alkylamine for M/S separation [124,125,126,127,128,129,130], polymers such as fluorene-based ones for extracting specific ( n , m ) structure [66,89,131,132,133], poly(phenylenevinylene) [134,135,136,137,138] and designed host molecules such as tweezer-type ones for discrimination of diameter, ( n , m ) and handedness [26,28,29,34]. Although the SWNTs have been optically resolved by selective solubilization with chiral nanotweezers [26,27,28,29] and DGU with chiral detergent [25,30], the absolute configuration of the resolved SWNTs were determined only by theoretical calculations [139].…”
Section: Chemical Methods For Separation Of Carbon Nanotubesmentioning
confidence: 99%
“…If the agent can recognize the electrical property and/or structural character of SWNTs, separation of SWNTs can be realized through the extraction [123]. The solubilizing agents reported so far include simple molecule such as alkylamine for M/S separation [124,125,126,127,128,129,130], polymers such as fluorene-based ones for extracting specific ( n , m ) structure [66,89,131,132,133], poly(phenylenevinylene) [134,135,136,137,138] and designed host molecules such as tweezer-type ones for discrimination of diameter, ( n , m ) and handedness [26,28,29,34]. Although the SWNTs have been optically resolved by selective solubilization with chiral nanotweezers [26,27,28,29] and DGU with chiral detergent [25,30], the absolute configuration of the resolved SWNTs were determined only by theoretical calculations [139].…”
Section: Chemical Methods For Separation Of Carbon Nanotubesmentioning
confidence: 99%
“…The CNTs formed a stable dispersion in the organic solution of PPVs, suggesting the formation of the polymer-wrapped CNTs. In addition to the dispersion of CNTs [ 66 82 ], the PPV wrapping was also utilized for the extraction of single-walled carbon nanotubes (SWCNTs) with specific chiral indices. Keogh et al and Coleman et al used the poly( m -phenylene-co-2,5-dioctoxy- p -phenylenevinylene) (PmPV, figure 5 ) to preferentially disperse SWCNTs with specific chiral indices, leaving the others in the precipitate [ 83 86 ].…”
Section: Type Of Polymer For Wrappingmentioning
confidence: 99%
“…5,19,20 Conversely, when non-covalent functionalization is used, the structural integrity of carbon nanotubes remains unchanged, allowing retention of the CNT properties, and enabling the use of both their conductive and mechanical properties in eventual applications. It has been shown that various conjugated structures, such as pyrene, 19,21,22 porphyrins, [12][13][14] and p-conjugated polymers 10,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] can form supramolecular complexes with nanotubes, and the resulting complex materials exhibit good solubility. In recent years, composite materials based on conjugated polymers and SWNTs have generated significant interest due to the combination of optical, electrical, and processability properties of the conjugated polymers with the strength and conductivity properties of carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, composite materials based on conjugated polymers and SWNTs have generated significant interest due to the combination of optical, electrical, and processability properties of the conjugated polymers with the strength and conductivity properties of carbon nanotubes. A number of conjugated polymers, including poly(mphenylene vinylene) (PmPV), [23][24][25][26][27] poly(thiophene) (PT), [28][29][30][31][32][33][34][35] poly-(phenylene ethynylene) (PPE), 10,41,42 and poly(fluorene) [36][37][38][39][40] have been successfully used to modify and strongly interact with the carbon nanotube surface through p-stacking or helical wrapping.…”
Section: Introductionmentioning
confidence: 99%